CGIAR research helps UNHCR integrate climate and nature data into global operations - Taiwo, Ibukun (2025)
More than 90 million refugees and internally displaced people live in places where climate shocks and environmental degradation increasingly shape daily risks. Floods, droughts, heat stress, and ecosystem loss now affect not only why people are displaced, but also how safe and viable displacement settings remain over time. Yet until recently, humanitarian operations have had limited tools to systematically assess and anticipate these risks.